1987
DOI: 10.1590/s0004-282x1987000300012
|View full text |Cite
|
Sign up to set email alerts
|

Esquistossomose medular: forma tumoral. Relato de um caso

Abstract: A case of schistosomiasis of the spinal cord is presented. A 16 years old boy developed a progressive spinal cord compression syndrome suggesting an intramedullary tumor. At the operation a granulomatous mass of the conus and epiconus was found and partially resected. The histopathological examination showed a granulomatous reaction surrounding Schistosoma mansoni eggs. The authors review the various aspects of spinal cord schistosomiasis, particularly the tumoral or granulomatous form. A comprehensive review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

1999
1999
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 29 publications
0
1
0
3
Order By: Relevance
“…This aspect has also been observed in some reported cases. [12][13][14][15][16][17] Spontaneous stabilization of the manifestations (followed or not by improvement), or development of transitory neurological dysfunction (particularly urinary retention) preceding the definitive installation of the myeloradicular picture were also some of the modalities of disease course observed in some of our patients and reported in the literature. 4;17-24 The proportion of patients who presented pain in the present study was higher than that reported in the review by Ferrari.…”
Section: Clinical Aspectsmentioning
confidence: 93%
“…This aspect has also been observed in some reported cases. [12][13][14][15][16][17] Spontaneous stabilization of the manifestations (followed or not by improvement), or development of transitory neurological dysfunction (particularly urinary retention) preceding the definitive installation of the myeloradicular picture were also some of the modalities of disease course observed in some of our patients and reported in the literature. 4;17-24 The proportion of patients who presented pain in the present study was higher than that reported in the review by Ferrari.…”
Section: Clinical Aspectsmentioning
confidence: 93%
“…O cerebelo raramente é acometido 3 . A disseminação mielorradicular é mais freqüente 1,2,7,16,19,20,25,26 , provavelmente devida a fatores anatômicos 25,27,30 . As crianças são acometidas em uma proporção menor que os adultos 23,26 .…”
Section: Discussionunclassified
“…Nosso caso apresentava granulomas envolvendo ovos de Schistosoma mansoni, portanto, com grande reação imunogênica e incluindo-se, assim, na forma pseudotumoral cerebelar 25,27 . De acordo com a literatura consultada, encontramos apenas um caso descrito com comprometimento cerebelar 3 e cujos aspectos cirúrgicos e laboratoriais muito se assemelhavam aos do nosso caso.…”
Section: Figuraunclassified
See 1 more Smart Citation